Antagonism of Corticotrophin‐Releasing Factor Type 1 Receptors Attenuates Caloric Intake of Free Feeding Subordinate Female Rhesus Monkeys in a Rich Dietary Environment. (January 2015) - Moore, C. J.; Johnson, Z. P.; Higgins, M.; Toufexis, D.; Wilson, M. E.
<x xml:space="preserve">Abstract</x> Social subordination in macaque females is a known chronic stressor and previous studies have shown that socially subordinate female rhesus monkeys consume fewer kilocalories than dominant animals when a typical laboratory chow diet is available. However, in a rich dietary environment that provides access to chow in combination with a more palatable diet (i.e. high in fat and refined sugar), subordinate animals consume significantly more daily kilocalories than dominant conspecifics. Substantial literature is available supporting the role of stress hormone signals in shaping dietary preferences and promoting the consumption of palatable, energy‐dense foods. The present study was conducted using stable groups of adult female rhesus monkeys to test the hypothesis that pharmacological treatment with a brain penetrable corticotrophin‐releasing factor type 1 receptor (CRF1) antagonist would attenuate the stress‐induced consumption of a palatable diet among subordinate animals in a rich dietary environment but would be without effect in dominant females. The results show that administration of the CRF1 receptor antagonist significantly reduced daily caloric intake of both available diets among subordinate females compared to dominant females. Importantly, multiple regression analyses showed that the attenuation in caloric intake in response to Antalarmin (Sigma‐Aldrich, St Louis, MO, USA) was significantly predicted by the frequency of submissive and aggressive behaviour emitted by females, independent of social status. Taken together, the findings support the involvement of activation of CRF1 receptors in the stress‐induced consumption of excess calories in a rich dietary environment and also support the growing literature concerning the importance of CRF for sustaining emotional feeding.